Relationship Banking in the Residential Mortgage Market? Evidence from Switzerland - Martin Brown; Matthias Hoffmann (Swiss Journal of Economics and Statistics, 2016)
Summary We examine to what extent mortgage lending is characterized by strong relationships between banks and their borrowers. Our analysis is based on survey data covering all current bank relations for a sample of 1,481 Swiss households out of which 687 have a mortgage. We document that mortgage borrowers maintain significantly more bank relations than comparable households without a mortgage. However, this does not imply that mortgage relations are loose. Comparing mortgage relations to other bank relations of the same households we find that mortgage relations are used for a broader scope of transactions and are held with banks that are located closer to the household. Examining the heterogeneity of mortgage relations across households, we find that financially sophisticated households are less likely to hold their mortgage with a local bank.